Is there a difference in ovarian reserve biomarkers and ovarian response between the right and left ovaries?. Issue 3 (September 2020) - Abrahami, Noa; Izhaki, Ido; Younis, Johnny S.
Abstract: Research question: Is there a difference in ovarian reserve biomarkers and ovarian response between the right and left ovaries of infertile women undergoing IVF treatments? Design: A total of 100 infertile women aged 27 to 37 years, diagnosed with either unexplained male factor or mechanical factor infertility, participated in the study. All women had both ovaries intact, and regular menstrual cycles with no previous diagnosis of polycystic ovaries or endometriosis. The data were collected separately for each ovary, and included parameters of basal sonographic ovarian reserve, as well as ovarian response to ovarian stimulation. Results: Basal sonographic ovarian reserve markers were similar between the two ovaries. The right and left ovaries did not differ in their basal antral follicle count (AFC) (6.9 ± 3.9 versus 6.8 ± 3.8, respectively, P = 0.672), nor did they differ in their ovarian volume (10.3 ± 6.7 versus 9.8 ± 8.0 cm 3, respectively, P = 0.636). Nevertheless, a superior right-sided ovarian response to ovarian stimulation was observed, with a significantly higher total number of follicles in the right compared with the left ovary (7.8 ± 4.3 versus 6.8 ± 4.2 follicles, respectively, P = 0.006), and a higher number of follicles ≥14 mm on the day of human chorionic gonadotrophin administration (4.9 ± 3.2 versus 3.8 ± 2.4 follicles, respectively, P = 0.002). Conclusions: Despite comparable basal AFC and ovarian volume, the two ovaries are distinguishable in their response to ovarian stimulation with a clear right-side preference. These findings imply that the superiority of right ovarian response may be derived from local pelvic factors, presumably a more efficient vascularization.